2021
DOI: 10.1038/s41419-021-04359-3
|View full text |Cite
|
Sign up to set email alerts
|

CD73-positive extracellular vesicles promote glioblastoma immunosuppression by inhibiting T-cell clonal expansion

Abstract: Extracellular vesicles are involved in the occurrence, progression and metastasis of glioblastoma (GBM). GBM can secrete a variety of tumour-derived extracellular vesicles (TDEVs) with high immunosuppressive activity that remotely suppress the systemic immune system, and therapy targeting TDEVs has potential efficacy. In this study, we detected a higher concentration of CD73+ TDEVs enriched in exosomes in central and peripheral body fluids of GBM patients than in those of patients with other brain tumours (low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The CD73 + TDEVs released by GBM cells could be taken up by T cells and inhibit cell cycle entry and clonal proliferation of T cells. Defects in exosome synthesis and CD73 expression remarkably repressed tumor growth in GBM-bearing mice and restored clonal proliferation of T cells in peripheral and central regions [ 75 ].…”
Section: The Roles Of Texs In Tmementioning
confidence: 99%
See 1 more Smart Citation
“…The CD73 + TDEVs released by GBM cells could be taken up by T cells and inhibit cell cycle entry and clonal proliferation of T cells. Defects in exosome synthesis and CD73 expression remarkably repressed tumor growth in GBM-bearing mice and restored clonal proliferation of T cells in peripheral and central regions [ 75 ].…”
Section: The Roles Of Texs In Tmementioning
confidence: 99%
“…Defects in exosome synthesis and CD73 expression remarkably repressed tumor growth in GBM-bearing mice and restored clonal proliferation of T cells in peripheral and central regions [ 75 ].…”
Section: The Roles Of Texs In Tmementioning
confidence: 99%
“…They can change the immune microenvironment, impacting chemo- and immune checkpoint blockers therapy. As such, cargos LGALS9 [ 38 ] and CD73 were identified [ 39 ]. In the central nervous system microglial cells EVs were determined to carry pro-inflammatory cytokine IL-1β and therefore to propagate inflammation [ 40 ].…”
Section: Extracellular Vesicles In Glioblastomamentioning
confidence: 99%
“…MDSC, Treg or DC expressing CD73 generate adenosine in tumours, which triggers the anti-inflammatory response via T-cells, macrophages, and natural killer cells (NK) [ 138 , 139 ]. Several studies have reported that the expression of CD73 in TEV also contributes to immunosuppression in different cancers [ 140 , 141 ]. TEV transfer CD73 to T-cells and inhibit their cell cycle entry and clonal proliferation by increasing adenosine [ 140 ].…”
Section: Tev Characterisationmentioning
confidence: 99%
“…Several studies have reported that the expression of CD73 in TEV also contributes to immunosuppression in different cancers [ 140 , 141 ]. TEV transfer CD73 to T-cells and inhibit their cell cycle entry and clonal proliferation by increasing adenosine [ 140 ]. Consistently, inhibition of TEV production or CD73 expression significantly inhibit tumour growth by restoring T-cell clonal proliferation [ 140 ].…”
Section: Tev Characterisationmentioning
confidence: 99%